Red Mud as an Adsorbent for Hazardous Metal Ions: Trends in Utilization - Maja Rajković; Ivana Jelić; Marija Janković; Dragi Antonijević; Marija Šljivić-Ivanović (Toxics)
The increasing importance of waste materials utilization with the necessary modification to remove various pollutants from industrial wastewater has been a research focus over the past few decades. Using waste material from one industry to solve pollution problems in another ultimately leads toward sustainable and circular approaches in environmental engineering, solving waste management and wastewater treatment issues simultaneously. In contemporary research and industry, there is a notable trend toward utilizing industrial wastes as precursors for adsorbent formation with a wide application range. In line with this trend, red mud, a byproduct generated during alumina production, is increasingly viewed as a material with the potential for beneficial reuse rather than strictly a waste. One of the potential uses of red mud, due to its specific composition, is in the removal of heavy metal and radionuclide ions. This study summarizes red mud’s potential as an adsorbent for wastewater treatment, emphasizing techno-economic analysis and sorption capacities. An overview of the existing research includes a critical evaluation of the adsorption performance, factors influencing efficiency rather than efficacy, and the potential for specific pollutant adsorption from aqueous solutions. This review provides a new approach to a circular economy implementation in wastewater treatment while guiding future research directions for sustainable and cost-effective solutions.